2018
DOI: 10.1098/rspb.2018.1735
|View full text |Cite
|
Sign up to set email alerts
|

Seasonally sympatric but allochronic: differential expression of hypothalamic genes in a songbird during gonadal development

Abstract: Allochrony, the mismatch of reproductive schedules, is one mechanism that can mediate sympatric speciation and diversification. In songbirds, the transition into breeding condition and gonadal growth is regulated by the hypothalamic–pituitary–gonadal (HPG) axis at multiple levels. We investigated whether the difference in reproductive timing between two seasonally sympatric subspecies of dark-eyed juncos ( Junco hyemalis ) was related to gene expression along the HPG axis. During the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…However, in three-spined stickleback, a fish expressing two GnRH isoforms, mRNA expression levels of GnRH3 were significantly elevated in spawning fish but downregulated in post-spawning fish [ 36 ], where GnRH3 acts as GnRH1 [ 47 ]. It is believed that reproductive development and gonadal recrudescence are controlled by top-down stimulation of the BPG axis via GnRHs and GtHs with hypothalamic sensitivity to sex steroids providing negative feedback, respectively [ 48 ]. It has also been demonstrated that the capacity of high-affinity GnRH binding sites (presumably representing receptors) might be higher in the breeding season fish than that in the post-breeding season fish [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in three-spined stickleback, a fish expressing two GnRH isoforms, mRNA expression levels of GnRH3 were significantly elevated in spawning fish but downregulated in post-spawning fish [ 36 ], where GnRH3 acts as GnRH1 [ 47 ]. It is believed that reproductive development and gonadal recrudescence are controlled by top-down stimulation of the BPG axis via GnRHs and GtHs with hypothalamic sensitivity to sex steroids providing negative feedback, respectively [ 48 ]. It has also been demonstrated that the capacity of high-affinity GnRH binding sites (presumably representing receptors) might be higher in the breeding season fish than that in the post-breeding season fish [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migrant and resident male juncos also differ in reproductive timing in common‐garden conditions (Fudickar et al, ). At the end of March, migrant males have significantly smaller testes and lower levels of testosterone than residents, but do not differ in mRNA transcript abundance of reproductive hormone receptors in the testis (Bauer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The liver responds to E2 in the bloodstream in order to produce yolk precursors, vitellogenin (VTG) and very‐low‐density lipoprotein (VLDL), which provides the protein and fat to the yolk. Modified from figure in Bauer et al, …”
Section: Introductionmentioning
confidence: 99%
“…Prior research on this system using transcriptomics and quantification of specific target genes has shown variation in gene expression in tissues related to the phase lag in the timing of reproduction in migrants as compared to residents, including muscle, blood, and brain (Fudickar et al, 2016a;Bauer et al, 2018;Singh et al, under preparation). But to our knowledge, prior research has not quantified neuroendocrine proteins as a functional correlate for reproductive timing and migratory preparedness.…”
Section: Discussionmentioning
confidence: 99%